Pengembangan Bahan Ajar Teks Proseur Berbasis Teknologi untuk Meningkatkan HOTS Siswa Kelas X SMA N 1 Badar - Santriana; Liesna Andriany; Ali (Medan Resource Center, 2022)
This research is aimed to know the feasibility of electronic module-based teaching materials for flip-books in class X SMA. The method used is the 4-D (four D) research method by S. Thiagarajan and the development steps are (1)Define, (2) Design, (3) Development, and (4) Dissemination. The source of data is a questionnaire. The type of data is quantitative descriptive data as the main data collected through an instrument by Likert scale. The respondents are material/language experts, design experts and media experts. The researcher used the validation stage by four expert validators, therefor it could be tested in a limited way, carried out for the dissemination stage. The material expert responses to teaching materials and obtained an average as 83% of all aspects or